2016
DOI: 10.1016/j.jcps.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

How inferred contagion biases dispositional judgments of others

Abstract: Drawing on recent evidence suggesting that beliefs about contagion underlie the market for celebrity‐contaminated objects, the current work investigates how people can make biased dispositional judgments about consumers who own such objects. Results from four experiments indicate that when a consumer comes in contact with a celebrity‐contaminated object and behaves in a manner that is inconsistent with the traits associated with that celebrity, people tend to make more extreme judgments of them. For instance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Sensitivity to disgust was assessed using eight items derived from the scale developed by Haidt et al (1994). For the purpose of our study, we used a selective procedure similar to that of past research (Hingston, McManus, & Noseworthy, 2017;Newman & Dhar, 2014;Newman et al, 2011). We only used items related to food behaviors: six items were selected from the core disgust dimension and two from the contamination disgust dimension (Olatunji, Haidt, McKay, & David, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Sensitivity to disgust was assessed using eight items derived from the scale developed by Haidt et al (1994). For the purpose of our study, we used a selective procedure similar to that of past research (Hingston, McManus, & Noseworthy, 2017;Newman & Dhar, 2014;Newman et al, 2011). We only used items related to food behaviors: six items were selected from the core disgust dimension and two from the contamination disgust dimension (Olatunji, Haidt, McKay, & David, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…A few studies have tested the underlying principle of the MTM by applying the law of contagion (Hingston, McManus, & Noseworthy, 2016;Newman et al, 2011). Contagion is when a consumer believes that immaterial symbolic meanings of a product are 'magically' transferred to themselves and imagine that somehow they are similar to the endorsing celebrity because they consume the endorsed product (Belk, 1988).…”
Section: Meaning Transfer Modelmentioning
confidence: 99%
“…For example, Hingston, McManus, and Noseworthy () found that when consumers are in contact with a celebrity‐contaminated object, people expect that they will perform in a consistent way with the celebrity, and if they do not (i.e., if they perform poorly in a task in which the celebrity excels), then those objects are evaluated more negatively. However, this negative product evaluation occurs only when there is an initial expectation created by the celebrity‐contaminated object.…”
Section: Theoretical Backgroundmentioning
confidence: 99%